CHICKEN-AND-EGG DILEMMA BETWEEN INCOME AND ALMS: REVIEW OF ISLAMIC PERSPECTIVES - Fitri Nurjanah; Mutiara Sakinah; Askar Muhammad (Universitas Airlangga, 2021)
Indonesia is the most generous country in the world. This is evident from the World Giving Index created by the Charities Aid Foundation which has placed Indonesia in the number one position in the world in 2018. There is an increase compared to the previous year, where Indonesia was in second place after Myanmar. The main indicators are the level of donating money, helping foreigners, and participating in volunteer activities. On the other hand, the World Bank in 2018 placed Indonesia in the sixteenth position based on GDP Current USD and the eighth position based on GDP PPP Current USD. This proves that income is not the main thing that encourages someone to give alms. However, it is still uncertain whether income and level of alms correlate with each other. Jones and Posnett (1991) revealed that an increase in the behavior of giving alms is not in line with an increase in household income. On the other hand, there is a significant positive relationship between income and a person's level of alms (Arshad, 2016). The two types of research mentioned (Jones and Posnett, 1991; Arshad, 2016) conducted testing at the micro level. Therefore, this research will concentrate more on the macro level. Pharoah and Tanner (1997) explain that people who consider religion important in their lives tend to give more. This study uses a quantitative approach to test the correlation between the World Giving Index and GDP using the Spearman rank correlation test. The Spearman rank correlation test measures the correlation between two random variables based on ranking order. The author has found that there is no correlation between high income and the desire to give alms. This research can be used as a reference for the Indonesian government to reduce inequality and poverty in the country by realizing the potential of alms in Indonesia.